2021
DOI: 10.1038/s41385-021-00438-y
|View full text |Cite
|
Sign up to set email alerts
|

Decreased production of epithelial-derived antimicrobial molecules at mucosal barriers during early life

Abstract: Young age is a risk factor for respiratory and gastrointestinal infections. Here, we compared infant and adult mice to identify age-dependent mechanisms that drive susceptibility to mucosal infections during early life. Transcriptional profiling of the upper respiratory tract (URT) epithelium revealed significant dampening of early life innate mucosal defenses. Epithelial-mediated production of the most abundant antimicrobial molecules, lysozyme and lactoferrin, and the polymeric immunoglobulin receptor (pIgR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Profound changes in the respiratory microbiota during the first days of life have a strong impact on immune maturation processes during this period, particularly on anti-viral immunity ( 44 46 ). Furthermore, multiple studies provided evidence for specific immune maturation processes during the first 2 weeks of a mouse life, such as increased epithelial production of antimicrobial peptides ( 47 ), DC functions ( 48 , 49 ), frequency of lung resident T cells ( 50 ) and AMs ( 51 ), and advanced Th1 differentiation ( 48 , 52 ). Considering that S. aureus is the leading cause of infection in the setting of critical illness and injury, our finding of enhanced anti- S. aureus immunity after neonatal IAV exposure might add an important argument to the research area of neonatal vaccinology.…”
Section: Discussionmentioning
confidence: 99%
“…Profound changes in the respiratory microbiota during the first days of life have a strong impact on immune maturation processes during this period, particularly on anti-viral immunity ( 44 46 ). Furthermore, multiple studies provided evidence for specific immune maturation processes during the first 2 weeks of a mouse life, such as increased epithelial production of antimicrobial peptides ( 47 ), DC functions ( 48 , 49 ), frequency of lung resident T cells ( 50 ) and AMs ( 51 ), and advanced Th1 differentiation ( 48 , 52 ). Considering that S. aureus is the leading cause of infection in the setting of critical illness and injury, our finding of enhanced anti- S. aureus immunity after neonatal IAV exposure might add an important argument to the research area of neonatal vaccinology.…”
Section: Discussionmentioning
confidence: 99%
“…Forced oscillometry: A subset of P14 mice not used for morphometry or transcriptomics were sedated with ketamine and xylazine via I.P. injection, and the flexiVent system (SCIREQ) was used to assess respiratory resistance and compliance as described (15,17). Briefly, the mice were tracheotomized with the appropriately sized cannula secured with a silk ligature.…”
Section: Further Methods Detailsmentioning
confidence: 99%
“…Having shown that exposure to supraphysiologic oxygen resulted in depressed expression of intestinal AMPs and an altered microbiome, we next wanted to test if AMP expression drove this effect. Lysozyme is the principal AMP, and expression is reduced in early life on most mucosal surfaces 15 . To test if the suppression of AMP expression in hyperoxia-exposed mice might have functional consequences, we repeated the hyperoxia-exposure experiment above using nearly genetically identical mice (C57BL/6NCrl, Figure 3A).…”
Section: Augmentation Of Lysozyme Improves Lung Function In Hyperoxia...mentioning
confidence: 99%
“…A rich repertoire of HDPs is distributed widely in animals, particularly in the mucous epithelium of the digestive tract, respiratory tract, genital tract, skin, and immune cells, which easily contact microorganisms. Accumulating data have shown that the differences in endogenous HDP expression are age-dependent, species-dependent, and tissue-dependent (Table ). HDP expression is either constitutive or induced, and the pattern is quite varied and complex.…”
Section: Distribution and Tissue Expression Specialties Of Hdpsmentioning
confidence: 99%